Dickinson's Misery : a Theory of Lyric Reading. - Jackson, Virginia, 1956- (Princeton University Press, 2013)
How do we know that Emily Dickinson wrote poems? How do we recognize a poem when we see one? In Dickinson's Misery, Virginia Jackson poses fundamental questions about reading habits we have come to take for granted. Because Dickinson's writing remained largely unpublished when she died in 1886, decisions about what it was that Dickinson wrote have been left to the editors, publishers, and critics who have brought Dickinson's work into public view. The familiar letters, notes on advertising fliers, verses on split-open envelopes, and collections of verses on personal stationery tied t.